THE INFLUENCE OF QUIZLET-BASED ARABIC LANGUAGE LEARNING MEDIA ON STUDENTS' LEARNING OUTCOMES IN THE 'HOBBIES' MATERIAL FOR EIGHTH GRADE AT MADRASAH TSANAWIYAH SWASTA AN-NIZAM MEDAN - Harahap, Berliana Sari; Taufiq, Muhammad (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This study aims to examine the effect of using Quizlet-based learning media on students' learning outcomes in the Arabic subject “Al-Hiwayat” (Hobbies) for Grade VIII at SMP Islam An-Nizam Medan. This research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. Data were collected through learning outcome tests administered before (pretest) and after (posttest) the implementation of Quizlet. Data analysis was conducted using SPSS, including tests of validity (content validity and construct validity via Pearson correlation), reliability (Cronbach's Alpha ≥0.7), normality (Kolmogorov-Smirnov or Shapiro-Wilk test), homogeneity (Levene's test), and paired sample t-test with a significance level of p < 0.05. Additionally, the N-Gain Score was analyzed to measure the effectiveness of the learning improvement. The results showed a significant difference between the pretest and posttest scores after using Quizlet, indicating that this medium effectively enhances students' learning outcomes in the “Al-Hawayat” material. The research results indicate that the use of Quizlet significantly improves students' learning outcomes in Arabic subjects, particularly in the topic of 'hobbies'.